Wanurejo Village Development Through Balkondes in Borobudur District Magelang Regency, Central Java - Amin Kiswantoro; Kiki Rizki Makiya; Rizky Maulana; Dwiyono Rudi Susanto; Nur Rohman (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
Wanurejo Village is one of the villages located in the Borobudur Temple area which is unique as a "Culture and Crafts" village and some of the factors that hinder the empowerment strategy in tourist villages are the increasingly egocentric nature that appears in individuals and tourism support facilities which still need to be improved. While the concept in the process of developing a tourist village, the surrounding community is used as an active subject, meaning that the surrounding environment and the social life of the people in the village are used as a tourist destination. The community also acts as a tourism promotion agent and innovator in providing ideas for developing tourist villages. The purpose of this research is to see how tourism village development is empowered to improve the economy in the village. This study uses a descriptive qualitative approach. Data collection was carried out through interviews with tourists, and village managers and through a literature review of previous research results. The results of the study show that in empowering a tourist village, careful planning is needed to advance the village economy, Balkondes is a good medium or forum to improve the economy of a tourist village which shows the superiority of the destination's attractiveness, of course, related parties to become pioneers in village empowerment the tour.